PENERAPAN LAPORAN KEUANGAN SEGMENTAL SEBAGAI ALAT PENILAIAN PRESTASI MANAJER PADA PERUM BULOG DIVRE SULUT DAN GORONTALO - Tatilu, Thefano Raldo Julian (Jurnal Berkala Ilmiah Efisiensi, 2015)
ABSTRACT The research objective is to investigate and analyze the application of Segment Performance Report that is used in assessing the performance division manager at Perum Bulog Divre Sulut and Gorontalo. The method used in this research is descriptive method, by comparing the actual income that has been set by management in accordance with the concept Perum Bulog Divre Sulut and Gorontalo Segment Performance Report. The results showed that the performance appraisal manager at Perum Bulog Divre Sulut and Gorontalo still conventional because it is still refers to the profit or loss generated by the division without seeing Â the contribution generated by the division in accordance with the concept of Segment Performance Report. But basically the performance of division manager is good. According to conventional reports, obtained ROI is 7.41% meanwhile according to Segment Performance Report, the resulting ROI is 12.83%. Keywords: Segment Performance Report, Perfromance Assesment Manager